Inflation rate and laboursâ wages in construction projects: economic relation investigation - Musarat, M.A. (Emerald Group Holdings Ltd., 2021)
Purpose: Labours are one of the key resources of construction projects having a significant impact on economic development. With time, the construction industry is getting a boom due to numerous construction projects in which laboursâ contribution is significant. Project betterment is associated with the project productivity which relates to the labours. Wages play a vital role in retaining labours in the construction industry. Design/methodology/approach: This study focuses on investigating the increasing and decreasing behaviour of labour wages in the construction industry and observing the impact of the inflation rate in deviating labour wages. Initially, the percentage deviation was calculated to observe the changing behaviour of the data and then the Spearman correlation test was used to find the relationship between the inflation rate and the labour wages. Findings: It is evident that even with a good economy and a stable construction sector, still, the labour wages faced a decline over time, which is a matter of concern. Also, based on the correlation coefficient, it was revealed that several labour wages categories are moderately and strongly correlated with the inflation rate and can impact project cost if the inflation rate is not considered while finalizing the budget. Besides that, the changing behaviour of labour wages due to the inflation rate impacts significantly on gross domestic product (GDP); therefore, it requires vital attention. Originality/value: Changes in labour wages are not considered in budget estimation which drag the project towards cost overrun. This study brings the attention of the stakeholders on the issue with experimental justification. Also, how the inflation rate is affecting the labour wages has also been addressed. Â© 2021, Emerald Publishing Limited.